Examining the differences between Ar Rahnu and conventional pawn broking in compatibility towards maqasid shariah / Salbiah Nur Shahrul Azmi, Nazimah Hussin and Rohaida Basiruddin (2015)
This paper is a theoretical paper that presents the differences between Ar Rahnu and conventional pawn broking in the intention to highlight why conventional pawn broking is not compatible with maqasid shariah while at the same time presenting that Ar Rahnu has conceptualized the application of maqasid syariah. This paper blends the theory of utility, the law of scarcity, information gathered from Quran and Sunnah with maqasid shariah in defending its arguments. From the blend, it is found that conventional pawn broking is deviated from the maqasid as opposed to Ar Rahnu. Ar Rahnu is revealed to offer a better alternative for pawner to have short term cash and property protection. In short, the paper establishes that although Ar Rahnu and conventional pawn broking serve the same function, the differences between these schemes highlights that the application of maqasid shariah is realizable in Ar Rahnu.